From study abroad to study at home: Spontaneous neuronal activity predicts depressive symptoms in overseas students during the COVID-19 pandemic - Li, Tong; Du, Xiaoyu; Zhang, Xiang; Dong, Aiping; Yuan, Xianshun; Yu, Tianyi; Diao, Ruiyuan; Duan, Shuai; Shen, Zijian; Yuan, Letian; Wang, Ximing (Frontiers in Neuroscience, 2023)
The objective of the study was to evaluate symptoms of depression and anxiety and the change in spontaneous neuronal activity in college students studying abroad during the coronavirus 2019 (COVID-19) pandemic. We examined functional brain changes using resting-state functional magnetic resonance imaging (MRI), amplitude of low-frequency fluctuations (ALFF), and regional homogeneity (ReHo) in overseas college students with enforced isolation due to the COVID-19 pandemic. Additionally, emotional assessments were utilized to rate the severity of depression and anxiety in the study-abroad students. The questionnaire results showed that anxiety and depressive symptoms differed between the overseas college students and the local college students. The MRI data showed altered ALFF and ReHo values in the superior medial frontal gyrus, precentral gyrus and paracentral lobule in the overseas students. In addition, for the overseas college students, the altered ReHo in the cluster including the left superior and medial frontal gyri, precentral gyrus, and paracentral lobule was significantly positively correlated with the Self-Rating Depression Scale scores. Thus, spontaneous brain activity in overseas college students changed during the COVID-19 pandemic. This change in brain function might be related to depression and anxiety symptoms. These results suggest that mental health services are needed to decrease the risk of anxiety and depression among college students studying abroad during the COVID-19 pandemic.